Interest in meta-research in geriatric medicine: a survey of members of the European Geriatric Medicine Society - SOYSAL, PINAR; Veronese, Nicola; SOYSAL, PINAR; Torbahn, Gabriel; Demurtas, Jacopo; Beaudart, Charlotte; Marengoni, Alessandra; Shenkin, Susan D.; Petrovic, Mirko; Sieber, Cornel C.; Cherubini, Antonio; Smith, Lee; et al. (My University, 2020)
Purpose There has been an exponential increase in meta-research, especially in the branch dealing with systematic reviews [SRs] and meta-analyses [MAs]. However, the knowledge regarding these topics in geriatric medicine is still poorly explored. We therefore undertook a survey of the current knowledge and needs in meta-research in geriatrics. Methods A short survey (taking approximately 5 min to complete) was freely available on the European Geriatric Medicine Society (EuGMS) website and disseminated via social networks by the EuGMS and the authors of the survey. The questionnaire was available during the whole year of 2019. The questionnaire specifically addressed demographic information, previous research activities and the knowledge of the participants on meta-research in geriatric medicine. Results The survey was completed by 291 participants from 36 different countries of about 20,000 EuGMS members (mostly with an age between 55 and 64 years; 51.5% female; mainly from Italy and Germany). Most respondents (65.6%) reported reading more than 20 articles in the past year, but few (36.4%) read more than 10 SRs/MAs. Participants reported that SRs and/or MAs are important in clinical practice: 83.8% giving a score of > 6/10, and 23.0% reporting 10. The large majority of the participants asked for more education in meta-research. In particular, there is need for educational courses for meta-research in geriatric medicine, online or in person, organized by the EuGMS. Conclusion Our survey shows that interest in SRs/MAs is high, and there is a demand for education on these topics in relation to geriatric medicine.